99mTc-hydroxydiphosphonate quantification of extracellular matrix mineralization in 3D human mesenchymal stem cell cultures - Großner, Tobias; Haberkorn, Uwe; Gotterbarm, Tobias (Bone & joint research, 2019)
Objectives: Bone tissue engineering is one of the fastest growing branches in modern bioscience. New methods are being developed to achieve higher grades of mineral deposition by osteogenically inducted mesenchymal stem cells. In addition to well established monolayer cell culture models, 3D cell cultures for stem cell-based osteogenic differentiation have become increasingly attractive to promote in vivo bone formation. One of the main problems of scaffold-based osteogenic cell cultures is the difficulty in quantifying the amount of newly produced extracellular mineral deposition, as a marker for new bone formation, without destroying the scaffold. In recent studies, we were able to show that 99mTc-methylene diphosphonate (99mTc-MDP), a gamma radiation-emitting radionuclide, can successfully be applied as a reliable quantitative marker for mineral deposition as this tracer binds with high affinity to newly produced hydroxyapatite (HA). Methods: Within the present study, we evaluated whether this promising new method, using 99mTc-hydroxydiphosphonate (99mTc-HDP), can be used to quantify the amount of newly formed extracellular HA in a 3D cell culture model. Highly porous collagen type II scaffolds were seeded with 1 × 106 human mesenchymal stem cells (hMSCs; n = 6) and cultured for 21 days in osteogenic media (group A - osteogenic (OSM) group) and in parallel in standard media (group B - negative control (CNTRL) group). After incubation with 99mTc-HDP, the tracer uptake, reflected by the amount of emitted gamma counts, was measured. Results: We saw a higher uptake (up to 15-fold) of the tracer in the OSM group A compared with the CNTRL group B. Statistical analysis of the results (Student`s t-test) revealed a significantly higher amount of emitted gamma counts in the OSM group (p = 0.048). Qualitative and semi-quantitative analysis by Alizarin Red staining confirmed the presence of extracellular HA deposition in the OSM group. Conclusion: Our data indicate that 99mTc-HDP labelling is a promising tool to track and quantify non-destructive local HA deposition in 3D stem cell cultures.
Im Titel ist "99m" hochgestellt
Gesehen am 04.12.2019